Bioconservadorismo e transhumanismo: a questão do melhoramento humano através das biotecnologias - Oliveira Júnior, Wagner Lafaiete de (2018)
The present work aims to analyze the problem of human enhancement through biotechnology from some theoretical and reflections more used in the discussion of their suitability or ethical inadequacy, and that we consider more important for a good evaluation. The first chapter gives a presentation on the problem of human biotechnological enhancement and some of the major conceptual dichotomies commonly used in the debate. To do so, we present a concept of human biotechnological enhancement as well as notions about technologies that may become part of biotechnological enhancement practices; we then deal with the dichotomous pairs internalism and externalism, natural and artificial, therapy and enhancement, and self enhancement and enhancement in future individuals. Chapter two exposes and analyzes the debate around the so-called ideal of conservation or Bioconservatism, a position that defends the unavailability of genetic patrimony to changes in breeding. We evaluate four arguments in favor of Bioconservatism, the arguments: human enhancement is an eugenic practice, enhancement reinforces unfair social contexts, enhancement increases social inequalities, the Slippery Slope argument. With the argumentative analysis, we conclude the chapter we showed that the Bioconservative position is neither solid nor adequate. In chapter three the Transhumanist position is presented, in which the biotechnological human enhancement is radically defended. We consider definitions and the document called The Humanist Declaration, prepared by a group of advocates of transhumanism. There is a detailed presentation of the transhumanist proposals of the philosopher Nick Bostrom and his table of transhumanist values, with critical attention to the problems arising from an unconditional acceptance of such a proposal. We then analyze the idea that the transhumanist proposal can only be effective if some of its auxiliary proposals are used as answers to the problems encountered in transhumanism; this would also raise other kinds of problems that seem to undermine the strength of the position. The conclusion of the chapter is that Transhumanism is also an inadequate position. In final considerations to the study, we summarize the points in which both the bioconservative proposal, and the transhumanist proposal are ethically problematic, and we support the proposal of a moderate human biotechnological enhancement, presented in its general lines, as the most reasonable so far.